THE EPIDEMIOLOGICAL SITUATION ON CHOLERA IN THE REPUBLIC OF KAZAKHSTAN IN 2011 - R. S. Musagaliyeva (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
The analysis of registered cholera cases that occurred during 1993-2008 showed that all epidemic cases of cholera in Kazakhstan were imported. The toxigenic cholera microbes were isolated from the water reservoirs which started in the neighbor country. The spatial distribution of non-toxic cholera vibrio has the regional features. The climatic and anthropogenic factors affect the distribution of the cholera vibrio in the Kazakhstan. The results of the analysis show that the complex approach has to be used for cholera epidemiological monitoring.